2021
DOI: 10.1038/s41598-021-90030-y
|View full text |Cite
|
Sign up to set email alerts
|

PapRIV, a BV-2 microglial cell activating quorum sensing peptide

Abstract: Quorum sensing peptides (QSPs) are bacterial peptides produced by Gram-positive bacteria to communicate with their peers in a cell-density dependent manner. These peptides do not only act as interbacterial communication signals, but can also have effects on the host. Compelling evidence demonstrates the presence of a gut-brain axis and more specifically, the role of the gut microbiota in microglial functioning. The aim of this study is to investigate microglial activating properties of a selected QSP (PapRIV) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“…Our study showed that SG could ameliorate CUMS-induced depression, and the underlying mechanism may be associated with improvements in gut microbiota composition and changes in intestinal inflammation and glutamate metabolism. It is known that microorganisms and the brain communicate with each other through the immune system, tryptophan metabolism, vagus nerve, and enteric nervous system ( Janssens et al, 2021 ). This communication involves a variety of microbial metabolites, such as pro-inflammatory factors, short-chain fatty acids, and neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that SG could ameliorate CUMS-induced depression, and the underlying mechanism may be associated with improvements in gut microbiota composition and changes in intestinal inflammation and glutamate metabolism. It is known that microorganisms and the brain communicate with each other through the immune system, tryptophan metabolism, vagus nerve, and enteric nervous system ( Janssens et al, 2021 ). This communication involves a variety of microbial metabolites, such as pro-inflammatory factors, short-chain fatty acids, and neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…QS peptides PapRIV produced by Bacillus cereus species have been found to be able to cross the gastrointestinal tract and the BBB and reach the brain to activate the production of proinflammatory cytokines by microglia leading to neurotoxic effects. 179 In vitro infection of macrophages by Group A Streptococcus was also found to inhibit their activation and production of proinflammatory cytokines through QS signalling. 183 The QS molecule N-3O-dodecanoylhomoserine lactone (3O-C12) produced by Pseudomonas aeruginosa (P. aeruginosa) is able to modulate immune responses through multiple mechanisms.…”
Section: The Interplay Between Microbial Qs and Their Mammalian Hostmentioning
confidence: 99%
“…Bacterial QS has also been found to modulate the functions of human neural and immune cells via a range of QS molecular targets that are expressed on the host cells 178,179 (Figure 3a). In a mouse study, three chemically diverse QS oligopeptides were found to be able to cross the BBB and influx into the mouse brain 180 .…”
Section: The Contribution Of Microbial Quorum Sensing In Cellular Def...mentioning
confidence: 99%
See 1 more Smart Citation
“…These permeability coefficients are higher than for other bioactive peptides, of which some have been detected in murine plasma in the past. 6 , 8 , 9 , 10 To explore the potential of iAM373 to cross the gut barrier and reach systemic circulation in vivo, germ‐free mice were inoculated with genetically modified E. coli that continuously produce iAM373. When the mice were treated with these bacteria through oral gavage, iAM373 was detected in the blood circulation; mice untreated or treated with unmodified E. coli (placebo) did not display iAM373 in their blood (Figure 2B,C ).…”
mentioning
confidence: 99%